The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/maco.201307104
|View full text |Cite
|
Sign up to set email alerts
|

Towards the mechanism of the accelerated corrosion of decorative nickel–chromium coatings in the presence of metals and their salts

Abstract: Microscopic studies suggested accelerated nickel corrosion to account for the extensive failure of decorative nickel chromium coatings. Electrochemical experiments further confirmed the crucial role of chloride, cupric, and ferric ion containing salts, which were found before on the corroded surface. Density functional theory calculations were used in the following to explain experimental observations and to obtain a detailed understanding of the mechanism of the accelerated corrosion under specific corrosive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It can be concluded that cupric ions are governing the cathodic reaction in Cu + Cl electrolyte. Moreover, the oxidising effect 20,21 accelerates the corrosion of bright nickel [16][17][18] as can be observed by the lateral progress of corrosion front found for active sites developed in Cu + Cl electrolyte (Fig. 4b).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It can be concluded that cupric ions are governing the cathodic reaction in Cu + Cl electrolyte. Moreover, the oxidising effect 20,21 accelerates the corrosion of bright nickel [16][17][18] as can be observed by the lateral progress of corrosion front found for active sites developed in Cu + Cl electrolyte (Fig. 4b).…”
Section: Resultsmentioning
confidence: 96%
“…However, research efforts were mainly focused on elucidating the harmful impact of chlorides for these systems. In the case of CASS test, despite the fact that cupric ions are increasing the corrosion rate for microporous nickelchromium coatings, 16,17 their impact in the corrosion mechanism is hardly defined. Recently, Electrochemical Impedance Spectroscopy (EIS) and Scanning Kelvin Probe (SKP) results have revealed that cuprous ions are involved in the corrosion process due to the reduction of cupric ions.…”
mentioning
confidence: 99%
“…While progress has been made in the last few decades, detailed mechanisms of passive film breakdown and pit initiation have not been provided yet. DFT has been a useful tool on studying the atomic scale interactions at surface and interface and potential mechanisms causing localized corrosion, including the interaction among different ions, [124][125][126] between ions and oxide film, 112,[124][125][126][127][128][129][130][131] between ions and bare metal surface, 90,[132][133][134] as well as the effect of defects. 112,131,[134][135][136] A few examples will be shown below.…”
Section: Localized Corrosionmentioning
confidence: 99%
“…112,[124][125] In an interesting paper from 2014, Schmidt, et al, presented a series of DFT calculations of metal/interfacial systems comprised of metal slabs with explicit water molecules, ions, and alloying elements. 134,137 A "progression of geometry optimizations" was shown illustrating differential reactivities of cupric and ferric chloride on Ni (111) with defects (steps)although, as stated in the above section on DFT methods, the progression of steps in a geometry optimization should not be interpreted as a step-wise reaction sequence, but rather as an algorithmic refinement to find an optimum energy state using steepest descents or conjugate gradients. In this way, the DFT has been used in more of a notional sense to convey mechanistic and energetic preferences, rather than absolute fundamental information regarding hypothetical reaction mechanisms.…”
Section: Localized Corrosionmentioning
confidence: 99%
“…4 However, the role of cupric ions has not been explored in detail during the corrosion of these coatings. In general, electrochemical methods 5 and quantum chemical ones 6 have shown the oxidising effect of cupric ions. This behaviour has been widely explored in aluminium and aluminium alloys after exposure to solutions containing Cu 2+ ions [7][8][9][10] as well as in the aluminium alloy 2024 after exposure to chloride-based electrolytes.…”
mentioning
confidence: 99%